Psoriasis treatment patterns and outcomes with ixekizumab in a real-world setting: results from a single US dermatology referral practice. (19th May 2022) - Leonardi, Craig; Tao, Rei; Setayeshgar, Solmaz; Wang, Sisi; Burge, Russel; Zhu, Baojin; Malatestinic, William N.
Abstract: Objective: To assess treatment patterns of Ixekizumab (IXE) and evaluate the speed of onset and long-term clinical and quality-of-life outcomes among a subset of patients who switched from adalimumab (ADA) and secukinumab (SEC) to IXE in a real-world setting. Method: A retrospective chart review study was conducted at a single US dermatology referral center. Result: 153 patients were included in the study, 69.3% of patients were biologic-experienced. ADA was the most commonly used biologic prior to IXE initiation. 66.7% of patients remained on IXE at the study end. 47.7% of patients received concomitant methotrexate, and usage decreased consistently after 1 month. IXE treatment duration was longer among patients who were early responders (achieved sPGA (0, 1) at 1 month) vs. non-early responders. 69.4% and 43.3% of patients who switched from ADA and SEC to IXE achieved sPGA (0, 1) by week 4, respectively. Conclusion: Patients who switched to IXE, specifically from ADA or SEC, had rapid treatment response as well as desirable long-term outcomes. IXE persistence was longer among early responders than non-early responders. Concomitant usage of methotrexate prior to switching to IXE and as a concomitant bridging treatment was reduced after IXE initiation while the proportion of patients achieving treatment targets remained high.